PENGUKURAN INFILTRASI DALAM KAWASAN TEKNOPARK PELALAWAN - Indriatmoko, Robertus Haryoto; Kristyawan, I Putu Angga; Shoiful, Ahmad (Jurnal Air Indonesia, 2015)
Teknopark Pelalawan area is an area designed as a center for the development of local advantages generated through research. In the region there will be College of Technology Palalawan and various Research and Development Center as to the development of local products, industrial downstream palm oil products, forest products and small and medium scale industries. Means and supporting facilities such as clean water, waste water and drainage systems are currently being incorporated into the master document teknopark region Palalawan plants. Infiltration measurements conducted to support the planning of drainage systems in order to manage rainwater in the area of teknopark Palalawan. This measurement is done in both land area units, namely: dry land units and land units of wet peat. Infiltration measurements done using an instrument called a double ring infiltrometer. To measure the rate of infiltration were analyzed using Kostiokov method. The result is: infiltration in the drylands of 1.5 mm / min on a peaty wetland was 0.4 mm / min. The conclusion that can be drawn is that in order to manage the rainwater would be more efficiently carried out on dry land unit.Ã‚Â Keywords: teknopark Pelalawan, infiltration rate, kostiakov, double ring infiltrometer, constant infiltration rate